Chapter 1 Picture Books, Gender and Multimodality: An Introduction - Moya- Guijarro, A. Jesús; Ventola, Eija (Taylor & Francis, 2022)
This collection offers a thorough treatment of the ways in which the verbal and visual semiotic modes interrelate toward promoting gender equality and social inclusion in children's picture books.